(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Polycystic Ovary Syndrome (PCOS)-recently recognized by medical organizations as Polyendocrine Metabolic Ovarian Syndrome (PMOS)-is a common endocrine disorder affecting women of reproductive age and is frequently associated with obesity, which may aggravate its clinical, metabolic, and hormonal manifestations. This study aimed to compare the clinical, metabolic, and endocrinal parameters between obese and lean women with PMOS. Aim: To find out the differences in the clinical, metabolic, and endocrinal parameters among obese and lean PMOS. Methods: A hospital-based cross-sectional analytical study was conducted in the Department of Obstetrics and Gynaecology, College of Medicine and Sagore Dutta Hospital, Kolkata, among 120 women diagnosed with PMOS according to the Rotterdam criteria. Results: Obese PMOS women had significantly higher BMI and waist-to-height ratio than lean PMOS women (p<0.0001). Acanthosis nigricans was more prevalent in the obese group (43.3% vs. 8.3%, p<0.0001). Metabolic assessment revealed significantly higher OGTT and fasting glucose levels among obese women (p<0.0001 and p=0.0069, respectively). Serum total testosterone was significantly elevated in obese PMOS patients, whereas the LH/FSH ratio was significantly higher in lean PMOS women (p<0.0001 for both). Fasting insulin, HOMA-IR, total cholesterol, LDL-C levels, and PMOS phenotype distribution showed no significant differences between groups. Phenotype A was the most common subtype in both lean and obese women. Conclusion: Obesity significantly worsens the clinical, metabolic, and endocrine manifestations of PMOS, particularly glucose metabolism and hyperandrogenism. Early identification and targeted weight-management strategies may help to reduce metabolic complications and improve reproductive outcomes in women with PMOS.